2021
DOI: 10.5171/2021.410043
|View full text |Cite
|
Sign up to set email alerts
|

Does A Good Strategy Help SMES’ Leaders in Managing a Crisis?

Abstract: Since more than a year, Covid-19 has been affecting everyone in every part of the world. The fear of death has imposed a series of never-ending lockdowns. Lockdowns came along with a financial crisis that has left all business sectors in wonder, especially the Small and Medium Enterprises (SMEs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…for the potential sales of Paraguayan MSMEs, which is comparable to studies of a similar nature carried out by Frangieh & Rusu (2021) and Mageto et al (2020). However, in line with Twahirwa et al findings from 2021, certain strategic choices, like the cancellation of planned investments, have been a major element that has also significantly impacted the likelihood of sales in Paraguayan MSMEs throughout the pandemic.…”
Section: Marconattosupporting
confidence: 81%
See 1 more Smart Citation
“…for the potential sales of Paraguayan MSMEs, which is comparable to studies of a similar nature carried out by Frangieh & Rusu (2021) and Mageto et al (2020). However, in line with Twahirwa et al findings from 2021, certain strategic choices, like the cancellation of planned investments, have been a major element that has also significantly impacted the likelihood of sales in Paraguayan MSMEs throughout the pandemic.…”
Section: Marconattosupporting
confidence: 81%
“…But in crisis situations, these actions are threatened, so in the pandemic context, MSMEs were forced to change their business model and strategy (Mitroff & Anagnos, 2001;Seeger et al, 1998;Mansor et al, 2021). For example, resorting to outsourcing some operations as a strategy to reduce costs as well as to maintain or even increase their sales (Frangieh & Rusu, 2021;Mageto et al, 2020;Rusu et al, 2020) Some recent studies, such as those conducted by Mageto et al (2022) and Zulkiffli and Padlee (2021), have found that the outsourcing of some operations has a positive effect on the business performance of MSMEs and is a valid strategy through which these types of companies can access capabilities that they lack internally at a lower cost. In this sense, the increasing use of this strategy of outsourcing certain operations, such as the delivery of products to the final customer during the pandemic, could have contributed to the improvement of sales performance in MSMEs.…”
Section: Msmesmentioning
confidence: 99%
“…To tackle with the events in the environment that potentially threaten organizational survival (Lengnick-Hall et al ., 2011), profitability and operational ability (Semerciöz et al ., 2015), firms choose special course of action, which is called strategic responses. Frangieh and Rusu (2021) show that when an SME's leader chooses a proper strategy, it strengthens the company, making it more flexible in anticipating and containing the crisis damages. Scholars have examined strategic responses to various kinds of adverse economic conditions from companies in different countries, sizes and backgrounds (e.g.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Puede adquirirse, estimularse, construirse con el tiempo y fortalecerse cuando se enfrenta a grandes problemas. Por ello, la formación de los directivos se ha convertido en una necesidad constante (Frangieh y Rusu, 2021).…”
Section: Escuelas De Pensamiento Estratégico: Liderazgounclassified